Caracterização físico-mecânica de painéis de partículas de bambu com adição de casca de café - Araújo, Isabella Imakawa de [UNESP] (2015)
Production of wood products and bamboo has been growing in recent years in search of a more rational use of these raw materials. Among these products are panels particles that combine sustainability and rational use of these materials. This paper aims at the study of the application of alternative raw materials in the manufacture of particle, using waste from industrial processing of coffee husk and bamboo. The twenty panels of particles were produced in three layers with bamboo species Dendrocalamus giganteus and adding particles of coffee hulls in the middle layer of the panel, joined by a polurethane-based resin castor. Physico-mechanical characterization was performed based on the specifications of NBR 14810-3/2006, canceled and its successor NBR 14810/2013. The physical properties of water absorption were evaluated for 24 hours, thickness swelling for 24 hours, density and moisture content. The mechanical properties were perpendicular traction, bending determine the modulus of rupture and modulus of elasticity and the top screw pullout and surface. The were also evalluated microscopically using a Scanning Electron Microscope. With this work is was concluded that the panel make with the panel of particles plus 10% and 30% cofee pods can be used commercially, as are internal use, non-structural use, non-strucutural and dry conditions. All properties with minimum requirements established by the Brazilian NBR 14.810/2013 were met